Jakers! the adventures of Piggley Winks. Wish upon a story [videorecording (DVD)] (Parthenon Entertainment, 2014)
In present day, Piggley lives with his three grandchildren and their mother. Whenever the children have a problem, Piggley tells them one of his childhood stories as a moral lesson. With flashbacks to 1950s Ireland, it shows Piggley with his friends and family and the lessons he learned. The grandchildren are able to identify core preschool themes such as storytelling, integral relationships and importance of family.